Hypoxia Is Not a Main Stress When Mycobacterium tuberculosis Is in a Dormancy-Like Long-Chain Fatty Acid Environment - Del Portillo, Patricia; García-Morales, Lázaro; Menéndez, María Carmen; Anzola, Juan Manuel; Rodríguez, Juan Germán; Helguera-Repetto, Addy Cecilia; Ares, Miguel A.; Prados-Rosales, Rafael; Gonzalez-y-Merchand, Jorge A.; García, María Jesús (Frontiers in Cellular and Infection Microbiology, 2019)
The capacity of Mycobacterium tuberculosis (Mtb) to sense, respond and adapt to a variable and hostile environment within the host has made it one of the most successful human pathogens. During different stages of infection, Mtb is surrounded by a plethora of lipid rich molecules and current evidence points out the relevance of fatty acids during the infectious process. In this study, we have compared the transcriptional response of Mtb to hypoxia in cultures grown in both, a mix of either even long-chain fatty acids or dextrose as carbon sources. Using RNA sequencing, we have identified the differential expressed genes in early and late hypoxia defined according to the in vitro Wayne and Hayes model and compared the results with the exponential phase of growth in both carbon sources. Our results showed that, different to dextrose, the number of genes overexpressed in hypoxia in the lipid medium was quite low in both, early and late hypoxia in all functional categories described for Mtb. The exceptions were the transcripts of stable and non-coding RNAs which were more expressed in the fatty acid medium. We found that sigB and sigE were overexpressed in the early phase of hypoxia, confirming their pivotal role in early adaptation to low oxygen concentration independently of the carbon source. A drastic contrast was found with the transcriptional regulatory factors at early hypoxia. Only 2 transcriptional factors were overexpressed in early hypoxia in the lipid medium compared to 37 that were overexpressed in the dextrose medium. Instead of Rv0081, known to be the central regulator of hypoxia in dextrose, Rv2745c, (ClgR), is playing a main role in hypoxia in the fatty acids medium. The low level of genes associated to the stress-response, showed by Mtb during their adaptation to hypoxia in fatty acids, suggested that this lipid environment makes hypoxia a less stressful condition for the tubercle bacilli. Therefore, when the bacillus is surviving in that environment its metabolism seemed to be already adapted to different stresses within the host, including hypoxia. This fact could explain the success of Mtb to establish long-term survival during latent infection.